Current treatment modalities for dry eye disease - E.B. Tatarnikova; O.I. Krivosheina (РМЖ "Клиническая офтальмология")
E.B. Tatarnikova, O.I. Krivosheina Siberian State Medical University, Tomsk, Russian Federation For many years, dry eye disease (DED) is a common ophthalmic condition associated with ocular surface damage and loss of homeostasis of the tear film. The key pathogenic factors of DED are tear film instability and tear hyperosmolarity, ocular surface inflammation and damage, and neurosensory alterations. Current treatment for DED consists of non-medical therapies, tear substitutes, anti-inflammatory agents, and surgical procedures. These treatments improve disease course and quality of life. However, these treatments are largely palliative as long-term (and even life-long) installation of eye drops is required. Modern and effective treatments for DED are needed. This paper reviews domestic and foreign published data on the important therapies for DED and novel tools to promote symptom relief. These data are required for the understanding of the pharmacological effects of various drug classes prescribed for DED and early treatment initiation. Keywords: dry eye disease, tear replacement therapy, anti-inflammatory treatment, surgery, hyaluronic acid, preservatives. For citation: Tatarnikova E.B., Krivosheina O.I. Current treatment modalities for dry eye disease. Russian Journal of Clinical Ophthalmology. 2021;21(1):18–23. DOI: 10.32364/2311-7729-2021-21-1-18-23.